Dynamic Adaptive API Security Framework Using AI-Powered Blockchain Consensus for Microservices - Kaul, Deepak (International Journal of Scientific Research and Management (IJSRM), 2020)
The concept of microservices architecture has nowadays become popular in the development of most software systems due to their benefits of application modularity and flexibility. Nevertheless, such architecture poses new security concerns especially on how to handle APIs that act as points of communication between different services. Traditional API protection strategies, based on predetermined patterns and a centralized platform, can be ineffective in guarding microservices because of the loosely connected structure of the latter. These limitations make APIs a sweet spot of highly skilled cyber threats like unauthorized data access, injection assaults, and Distributed Denial of Service (DDoS).This research presents a conceptual framework known as Dynamic Adaptive API Security Framework that uses Artificial Intelligence (AI) and blockchain technology to address these challenges. This first one uses AI to monitor API traffic and detect anomalies in real time with the help of the proposed framework. Through anomaly detection, machine learning models can detect unusual activity such as Suspicious usage patterns, patterns with malicious payloads, and pattern of many API calls. Also, AI offers an analytic feature, which can predict the vulnerability a certain target, based on data from previous attacks, and allow targeted prevention. Alongside AI, blockchain innovation is used to create an unalterable, distributed record of communication between API. Based on consensus mechanisms like Proof of Stake or Practical Byzantine Fault Tolerance, the framework guarantees the provenance of API transaction logs. These logs offer a great resource for the forensic activities in case of a breach of the system’s security. Also, smart contracts support even complex and constantly changing dynamic access control policies, adjusting as soon as AI-driven threat intelligence data is available. This synergy of using AI and blockchain in the framework generates an adaptable, transparent, and resilient security model that interfaces threats. Real-time anomaly detection together with immutable auditability integrated in the proposed framework improves the level of API security in microservices while simultaneously supporting GDPR and HIPAA compliance. This approach fills the gap in existing security solutions which cannot cope with the growing security issues in microservices format, providing a long-term solution for increasing security of complicated, decentralized microservices landscape.Summing up, this work presents a new comprehensive strategy to API security using the advantages of both AI and blockchain technologies. Applying the framework identifies how these technologies can be synchronously balanced and orchestrated to respond to threats, protect data input, and offer clear microservices security and foundation for the advancement of subsequent generation of software.